DEVELOPMENT AND APPLICATION OF MINING MACHINERY PLANETARY REDUCTION GEARS STRENGTH CHECK SOFTWARE - LIU XuNan; LI ChuiYang; ZHAO LiJuan; WANG AnRan (Jixie qiangdu)
The planetary gear strength checking software has been developed by combined programming of MATLAB and EXCEL. Take the contact normal force from mining machinery dynamics simulation as the input of the software with other necessary gear’s design and material parameters,the software can achieve gear tooth surface contact stress and root bending stress checking. The shortages of unable to determine the gear force in traditional analysis,unable to solve bending stress and solve contact stress for a long time by using the finite element software have been solved. Taking the EBZ220 roadheader as engineering object,though the checking result,the roadhead cutting unit’s second stage planetary gear’s root bending stress does not meet the strength requirement,that means this roadhead Not suitable for cutting rock,whose f value greater than 8 at the speed 1. 38 m/min. this research provides a new concept and method for gear strength checking,which has theoretical significance and strong engineering application value.